Fixation strategy influences the ability to focus attention on two spatially separate objects. - Stefanie Hüttermann (Public Library of Science (PLoS), 2013)
The ability to devote attention simultaneously to multiple visual objects plays an important role in domains ranging from everyday activities to the workplace. Yet, no studies have systematically explored the fixation strategies that optimize attention to two spatially distinct objects. Assuming the two objects require attention nearly simultaneously, subjects either could fixate one object or they could fixate between the objects. Studies measuring the breadth of attention have focused almost exclusively on the former strategy, by having subjects simultaneously perform one attention-demanding task at fixation and another in the periphery. We compared performance when one object was at fixation and the other was in the periphery to a condition in which both objects were in the periphery and subjects fixated between them. Performance was better with two peripheral stimuli than with one central and one peripheral stimulus, meaning that a strategy of fixating between stimuli permitted greater attention breadth. Consistent with the idea that both measures tap attention breadth, sport experts consistently outperformed novices with both fixation strategies. Our findings suggest a way to improve performance when observers must pay attention to multiple objects across spatial regions. We discuss possible explanations for this performance advantage.